Genotypic responses to different environments and reduced precipitation reveal signals of local adaptation and phenotypic plasticity in woodland strawberry - De-la-Cruz, Ivan M; Batsleer, Femke; Bonte, Dries; Diller, Carolina; Hytönen, Timo; Izquierdo, José Luis; Osorio, Sonia; Posé, David; de la Rosa; Aurora; Vandegehuchte, Martijn L; Muola, Anne; et al. (Oxford University Press (OUP), 2025)
BACKGROUND AND AIMS
Climate change is causing increasing temperatures and drought, creating new environmental conditions, which species must cope with. Plant species can respond to these shifting environments by escaping to more favorable environments, undergoing adaptive evolution, or exhibiting phenotypic plasticity. In this study, we investigate genotype responses to variation in environmental conditions (genotype-by-environment interactions; G × E) over multiple years to gain insights into the plasticity and potential adaptive responses of plants to environmental changes in the face of climate change.
METHODS
We reciprocally transplanted 16 European genotypes of Fragaria vesca (Rosaceae), the woodland strawberry, between four sites along a latitudinal gradient from 40°N (Spain) to 70°N (northern Finland). We examined G × E interactions in plant performance traits (fruit and stolon production and rosette size) under ambient weather conditions and a reduced precipitation treatment (as a proxy for drought), at these sites over two years.
KEY RESULTS
Our findings reveal signals of local adaptation for fruit production at the latitudinal extremes of F. vesca distribution. No clear signals of local adaptation for stolon production were detected. Genotypes from higher European latitudes were generally smaller than genotypes from lower latitudes across almost all sites, years and both treatments, indicating a strong genetic control of plant size in these genotypes. We found mixed responses to reduced precipitation: while several genotypes exhibited poorer performance under the reduced precipitation treatment across most sites and years, with the effect being most pronounced at the driest site, other genotypes responded to reduced precipitation by increasing fruit and/or stolon production and/or growing larger across most sites and years, particularly at the wettest site.
CONCLUSIONS
This study provides insights into the influence of different environments on plant performance at a continental scale. While woodland strawberry seems locally adapted in more extreme environments, reduced precipitation results in winners and losers among its genotypes. This may ultimately reduce genetic variation in the face of increasing drought frequency and severity, with implications for the species' capacity to adapt.